VD_FINDINFO ML / 2013 / 117 vom 6. Juni 2013 - VD Tribunal cantonal (2013)
DROIT D'ÊTRE ENTENDU, NOTIFICATION DE LA DÉCISION, PRÉSOMPTION IRRÉFRAGABLE | 136 CPC (CH), 138 al. 3 let. a CPC (CH), 138 CPC (CH)